Педагогічні умови формування професійно-мовленнєвої культури майбутніх фахівців із фізичного виховання та спорту в умовах навчання у ВНЗ - Кондрацька, Г.; Kondratska, G. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Розкрито педагогічні умови формування професійно-мовленнєвої культури майбутніх фахівців із фізичного виховання та спорту в умовах навчання у ВНЗ. Показано, на прикладі яких дисциплін можна розширити та поглибити їх мовленнєву культуру The pedagogical conditions of professionally verbal culture formation of the future specialists in physical education and sport in the conditions of higher educational establishment education process have been researched. The model of professionally verbal culture formation of future specialists has been worked out. A task, principles, stages and aspects of work, directions and types of activity, forms, methods and facilities, evaluation criteria have been defined. The example of disciplines is shown as a possible discipline to extend and deepen the verbal culture of specialist of physical
Pedagogical Conditions of Professional Verbal Culture Formation of the Future Specialists in Physical Education and Sport in the Conditions of Higher Educational Establishment Education
Keywords: мовленнєва культура; педагогічні умови; модель формування; фахівець фізичного виховання та спорту; verbal culture; pedagogical conditions; forming model; specialist of physical education and sport; 378.037